PENERAPAN PEMBIAYAAN GADAI EMAS DI BRI SYARIAH - NILA PRATIWI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
The problem in this research is how the contract Execution gold mortgage bank in BRI Syariah Padang. The objectives to be achieved in this research is to identify and analyze the implementation of the agreement pawning gold in BRI Syariah Padang. The method used in this study patterned Field Research with qualitative research. While the source of the data in this study were employees and customers of BRI Syariah. Data collection procedures that researchers do, observation, interviews, and documentation. The number of informants in this study was done by using Snowball Sampling (Snowball), the meaning is very dependent on the completeness of the data obtained in accordance with the purpose of the research is expected. The results of this study, BRI Syariah Padang continuously improve its performance based on Sharia Board Fatwa No.25 / DSN-MUI / III / 2002 and the National Sharia Board fatwa MUI No. 26 / DSN-MUI / III / 2002 on gold pawn, allowed gold mortgage based on the principle of rahn. It is evident that the product pawning gold in BRI Syariah Padang increasingly accepted and people interested in the city of Padang.